Análisis de las propiedades psicométricas de la Escala de Satisfacción Laboral (WES10) en docentes y personal administrativo de las universidades del Ecuador - Ramos Pardo, Jéssica Maribel (2018)
Abstract:The objective of the study was to analyze the psychometric properties of the instrument Working Environment Scale (WES-10) or work satisfaction scale, in terms of reliability and validity in a sample of 58 teachers and 42 administrative employees of the Universities of Ecuador. The analysis of reliability through internal consistency threw an α = 0.72, considered an acceptable value. Also, the validity of construct was analyzed through an exploratory factor analysis of which was obtained a bifactorial structure that explained 46.21% of the total variance; In addition, there was a differentiation of groups between sex and the role of participants, for which, no significant difference was found. Regarding the validity of the concurrent type, a positive correlation was found between the WES-10 and the LSQ (r =. 390). The data obtained suggest that the wes-10 is a reliable and valid instrument to measure satisfaction in the Ecuadorian labor context.